Penerapan Batik Bakaran Pada Pembuatan Bridal Gown The Application Of Bakaran Batik For Bridal Gown Making - Edi Suwasana; Dila Oktaviana Devani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Batik, especially Bakaran batik, has never been applied to bridal gowns because most bridal gowns tend to be plain white and are only decorated with Swarovski, sequins, and pearls. The problem of this research is how a Bakaran batik can be applied in bridal gown making. The purpose of this research is to understand the application of Bakaran batik in bridal gown making. The research method used is research and development. The results of a Bakaran batik application to the bridal gown making begin with a design determination. The design is a bridal gown inspired by the beauty of Indonesian artwork Bakaran batik. There is a Sido Mukti motive surrounding the bottom of the gown up to the tail, with a diverse arrangement of Sido Mukti motives that has a distinct meaning. After determining the design, it is continued by preparing the tools and materials, sizing up, shaping pattern, cutting material, spellbinding, sewing process, and finishing. The recommendation from the application of Bakaran batik on the bridal gown is that the design of a skirt for the crinoline would be best combined with the main part and lining fabric because it can affect the fall of the pleated detail. Completing the solution on the crinoline should use a finished seam from bias tape because the fibres on the crinoline are very sharp and can be uncomfortable or itchy if it is exposed to the skin.